2005
DOI: 10.4049/jimmunol.175.6.4091
|View full text |Cite
|
Sign up to set email alerts
|

Differential Calcium Regulation of Proinflammatory Activities in Human Neutrophils Exposed to the Neuropeptide Pituitary Adenylate Cyclase-Activating Protein

Abstract: The neuropeptide pituitary adenylate cyclase-activating protein (PACAP) acts via the G protein-coupled receptor vasoactive intestinal peptide/PACAP receptor-1 to induce phospholipase C/calcium and MAPK-dependent proinflammatory activities in human polymorphonuclear neutrophils (PMNs). In this study, we evaluate other mechanisms that regulate PACAP-evoked calcium transients, the nature of the calcium sources, and the role of calcium in proinflammatory activities. Reduction in the activity of PMNs to respond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 52 publications
1
23
1
Order By: Relevance
“…In fact, increases in [Ca 2ϩ ] i are believed to play an essential role in affecting cell movement and may activate downstream signaling pathways such as MAPK and possibly PI 3-kinase (1,5,22,26,43,46,47,49). Our data indicate that, in human pneumocytes, the CXCR3-A splice variant but not the CXCR3-B splice variant increases [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 63%
“…In fact, increases in [Ca 2ϩ ] i are believed to play an essential role in affecting cell movement and may activate downstream signaling pathways such as MAPK and possibly PI 3-kinase (1,5,22,26,43,46,47,49). Our data indicate that, in human pneumocytes, the CXCR3-A splice variant but not the CXCR3-B splice variant increases [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 63%
“…PACAP displays numerous functions in cells of neuronal and non neuronal origin and functional VIP/PACAP receptors have been demonstrated on PMNs, mediating Ca 2+ - dependent pro-inflammatory activities through the activation of multiple regulatory pathways [71]. Thus, it was demonstrated that the extracellular and intracellular Ca 2+ play key roles in PACAP mediated proinflammatory activities [72]. In addition, it has been reported that, in contrast to the inhibitory effect of CAT, PACAP may induce an increase of Ca 2+ entry and catecholamine release in bovine chromaffin cells by a a unique pathway distinct from nAChR, VOCs and SOCs [73].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, in neuronal cells, some effects of PACAP are mediated through a cAMP/EPACdependent, PKA-independent signaling cascade [41,42]. As we found previously that VPAC1 is differentially regulated in human neutrophils and monocytes [13][14][15][16], we evaluate in this study whether in monocytes, VIP can modulate signaling pathways and functions. In sharp contrast to what has been reported in neutrophils [43], we did find that human monocytes are sensitive to VIP.…”
Section: Introductionmentioning
confidence: 97%